Joint Programs in Vietnam in the Time of COVID-19 Pandemic: “A model” of Students’ Preference (What do Learners Care about?) - Huong Giang, Pham; Thuy Anh, Tu; Ngoc Oanh, Luong (VNU Journal of Science: Policy and Management Studies, 2021)
This study is among the first attempts to provide an understanding of factors affecting students’ intention to choose the joint programs for undergraduate education in Vietnam in the time of new normal context (i.e. COVID-19 pandemic). A questionnaire-based survey was employed to collect data from high school and undergraduate students. The Partial Least Square-Structural Equation Modeling (PLS-SEM) method is used to analyze the data collected. Overall, results show that the joint programs that are attractive to Vietnamese students/pupils should have international standardized content, include subjects that are highly applicable, qualification of teaching staffs. In terms of COVID-19 pandemic effect, the COVID-19 pandemic increases the probability of student choosing joint programs. This finding predicts that there may be a significant drop in the number of students studying the joint programs in Vietnam after the COVID-19 is under control as they may go to study abroad. Keywords: Joint program, Vietnam, student’s preference, PLS-SEM. References [1] R. Mellors-bourne, T. Hooley, J. Marriott, Understanding how people choose to pursue taught postgraduate study (2014). https://derby.openrepository.com/handle/10545/315917 [2] K. M. Elliott, D. Shin, Student Satisfaction: An alternative approach to assessing this important concept. Journal of Higher Education Policy and Management, 24(2) (2002) 197–209. https://doi.org/10.1080/1360080022000013518. [3] R.A. Peterson, W.R. Wilson, Measuring Customer Satisfaction: Fact and Artifact. Journal of the Academy of Marketing Science 20(1) (1992) 61–71. https://doi.org/10.1177/009207039202000106 [4] P. Sheppard, R. Smith, What students want: using a choice modelling approach to estimate student demand. Journal of Higher Education Policy and Management 38(2) (2016) 140–149 (in Vietnamese). https://doi.org/10.1080/1360080X.2016.1150236 [5] N.Q. Nghi, K.N. Huyen, P.Q. Cuong, L.K. Thanh, Factors affecting satisfaction on conducting scientific research among young lecturers in Can Tho University. Can Tho University Journal of Science, 51 (2017) 41-52. https://doi.org/10.22144/ctu.jvn.2017.093 [6] J. Hemsley-Brown, I. Oplatka, University choice: What do we know, what don’t we know and what do we still need to find out? International Journal of Educational Management, 29(3) (2015) 254–274. https://doi.org/10.1108/IJEM-10-2013-0150 [7] R. McManus, J. Haddock-Fraser, P. Rands, A methodology to understand student choice of higher education institutions: the case of the United Kingdom. Journal of Higher Education Policy and Management, 39(4) (2017) 390–405. https://doi.org/10.1080/1360080X.2017.1330806.